IMPLEMENTASI PENGOPERASIAN CCTV DI BANDARA INTERNASIONAL JAWA BARAT KERTAJATI - Ikhlasul Amal; Lela Nurpulaela (Peneliti.net, 2023)
(Closed Circuit Television) is a camera used to spy, monitor or record the condition of a location for security purposes. So the integrated camera will transmit a signal from somewhere to the monitor screen. This surveillance camera is an important device to be installed in areas that require more surveillance. Well, for those of you who want to know more about CCTV cameras, here is a review. CCTV is a tool that can record events or events without using an operator. Milestone XProtect Smart Client is software for monitoring cameras and other related components in one Video Management software system with the Milestone brand. Switches/Hubs are generally used in IP camera type CCTV networks to connect servers, client PCs and several CCTV cameras. Based on the transmission speed, a Switch/Hub with a transfer speed of 10/100Mbps and a Gigabit Ethernet Switch/Hub with a transfer speed of 1000Mbps